We'll bite your tail, Geronimo! - Stilton, Geronimo (Stilton, Geronimo. Spacemice ;, 2017)
"Professor Greenfur, the onboard scientist on spaceship MouseStar 1, has changed color from green to--orange! What's going on? To find out, the spacemice travel to his home planet of Photosyntheson. There, they learn that all of Professor Greenfur's relatives are being threatened by the nibblix, tiny aliens with very sharp teeth! Can the spacemice help in time?"--